Utilization of Quiz Kreator in Student Achievement Assessment in Elementary School - Chairuddin Chairuddin; Rahmat Hidayat; Nasruddin Nasruddin; Kamaruddeen Kadayloding; Erwin Prasetya Toepak (International Journal of Language and Ubiquitous Learning, 2024)
Background. The world of education is inseparable from various learning components. The utilization of technology cannot be separated from the world of education. One of them is the use of Quiz Kreator for student achievement assessment in elementary schools. Quiz Kreator is one of the online applications used to create quizzes, including multiple choice quizzes and true false quizzes. Purpose. This study aims to determine how student achievement in elementary schools after using the Quiz Kreator application in the learning process. Method. The researcher used quantitative research methods, namely by distributing questionnaires to elementary school students. The questionnaire was distributed online. Results. The results showed that the use of Quiz Kreator in assessing student achievement in elementary schools has a positive impact on students. The use of Quiz Kreator as an assessment tool that is well designed and relevant to the material being taught, can improve student achievement. Quiz Kreator can provide assessment results automatically and accurately. This can also help teachers in assessing student achievement more objectively. Conclusion. the use of Quiz Kreator in assessing student achievement in elementary schools can be utilized well. The use of this Quiz Kreator application can improve student achievement in the learning process.